Make it, gift it handmade gifts for every occasion - Bolte, Mari (North Mankato, MN Capstone Press, 2016)
Step-by-step instructions, tips, and full-color photographs will help teens and tweens create personalized presents"-
A gift from book Africa
Handcraft
1 2 13 15
NEW_ZTN_GN
Keywords: Gifts -- Juvenile literature; Gifts; Handicraft -- Juvenile literature